A história do esporte no ensino superior brasileiro de 1905 a 1930 - Vitor Lucas de Faria Pessoa (2022)
The aim of this research is to elaborate a historical analysis of how the development of the sporting phenomenon occurred within the institutions of higher education in Brazil from 1905 to 1930. Based on this, we seek to relate the sports sphere with the broader transformations that occurred in the country during the period that corresponds to the validity of the Primeira República. For that, documents and periodicals dated between 1905 and 1930 were used. The sources were collected in the collection of the Biblioteca Nacional do Rio de Janeiro through the Hemeroteca Digital Brasileira. In all, 2,094 occurrences about sport were analyzed within higher education institutions in the country in the time frame proposed by the research. The documents and sources come from several Brazilian states, including Rio de Janeiro, São Paulo, Minas Gerais, Santa Catarina, Pernambuco, Pará, Rio Grande do Sul and Paraná. As a theoretical perspective, we start from discussions about Cultural History and Theory of Associativism. Regarding the research results, we conclude that associativism was the main factor that contributed to the systematization of the sports phenomenon in higher education schools in the first three decades of the twentieth century. In addition, the processes triggered by modernity (urbanization, industrialization, commercialization) impacted the development of academic sport in the country, but played a secondary role when compared to "associative capital". Academic sport played an important role in the dissemination of bodily practices such as football, volleyball, athletics, chess, water polo, fencing and basketball in Brazil. Finally, unlike what happened with university sports from the 1930s onwards, academic sports observed in the first three decades of the 20th century did not suffer direct interference from the State, either from the executive or legislative bodies, which reaffirms the importance of civil associations to analyze the historical emergence of this cultural phenomenon.